Life during COVID-19 - Ternus, Lynn (COVID-19 pandemic (BrightPoint Press), 2021)
Examines what life was like during the COVID-19 pandemic, discussing how individuals altered their lives to slow the spread of the virus, alterations in school and work environments, government response, and the effect on businesses and employment. Includes color photographs, a glossary, and further resources.